Fiscal Decentralisation and Public Investment The Experience of Latin America - de Mello, Luiz (Paris OECD Publishing, 2010)
Despite large differences across countries, Latin America's average investment-to-GDP ratio and the overall quality of infrastructure in the region are relatively low by international comparison. Empirical evidence on the effects of fiscal decentralisation on investment based on a panel of Latin American countries since the late 1990 suggests that fiscal decentralisation discourages Latin American subnational governments from investing (acquiring fixed assets) and that lower subnational spending on investment is associated with lower economy-wide gross fixed capital formation. Latin American countries will therefore need to face a double challenge of revisiting the current arrangements for decentralised provision that discourage subnational governments from investing, while making the most of decentralisation as a policy lever to raise private investment
Keywords: Economics